6 key levers of a successful organizational transformation - White, A; Wheelock, M; Canwell, A; Smets, M (Harvard Business School Publishing, 2023)
Organizational transformations are extremely difficult on a personal level for everyone involved. A team of researchers found that in successful transformations, leaders not only made sure their teams had the processes, resources, and technology they needed — they also built the right emotional conditions. These leaders offered a compelling rationale driving the transformation, and they ensured employees had the emotional support they needed to execute. This meant that when the going inevitably got tough, employees felt appropriately challenged and ultimately energized by the stress. By contrast, leaders of the unsuccessful transformations didn’t make the same emotional investment. When their teams hit the inevitable challenges, negative emotions spiked, and the team entered a downward spiral. Leaders lost faith and looked to distance themselves from the project, which led employees to do the same. The researchers identified six behaviors that consistently improved the odds of transformation success.